#TITLE_ALTERNATIVE# - GILANG WAHAB (NIM 15104036); Pembimbing : Dr. Deni Suwardhi, ST., MT. dan Ir. Agoes S. Soedomo, ARKY
Most of mapping object on physical earth surface was in three dimensional (3D) form which automatically loose its information if representate in two dimensional (2D) plane. 3D object modeling require the highest quality data which acquisited from one of three modeling technique, there were Terrestrial Laser Scanner, Close Range Photogrametry, or Electronic Total Station. To comparing the geometry data quality from three of 3D object modeling technique, this study using 3D conformal transformation thus the checkpoint co-ordinate accuration level will be known from the value of root mean square residual, while for comparison angle and distance had done by computing residual value with trusted data. The object in this study were Boscha Observatorium and electricity center building as additional object. Base on instrument specification, error spreading, and data acquisitions process, this study assume that Electronic Total Station data is the right one. The biggest value of root mean square residual on X component which gotten by comparing Electronic Total Station and Close Range Photogrametry, while the biggest value of root mean square residual on Z component has gotten by comparing Electronic Total Station and Terrestrial Laser Scanner. From angle comparison it was found that co-ordinates difference get smaller value on a smaller angle which made of three coordinates, beside the distance comparison, it was found that distance difference get better if measurement has done in bigger distance. As a support of this study, there is a comparison about effectivity and efficiency of data acquisition and processing from those three modeling technique.